Analisis Wilayah Rawan Banjir DAS Cimanuk Menggunakan Model Complete Mapping Analysis dan SIG - Muhammad Azriel Sahid; Ilham Badaruddin Mataburu; Rayuna Handawati; Sony Nugratama Hijrawadi (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
The occurrence of flooding in the Upper Cimanuk Watershed has increased in recent years as a result of the decline in watershed quality due to changes in land use. A flood is the work accumulation of various environmental factors in a watershed. This study aims to identify the level of flood-prone and its determinants in the Cimanuk Hulu watershed. The method used in this study is the overlay method using GIS accompanied by weighting and scores determined by the Composite Mapping Analysis (CMA) model of 6 parameters, consist of Topographic Wetness Index (TWI), Land Use, Rainfall, Slope, Elevation, and Soil type. Flood event points as comparison parameters in determining scores and weights. The results showed that the variable land use was the variable with the highest weight of 27.01, respectively, affecting the level of flood-prone in the study area. The very high prone area includes an area of 1.57%, high prone area of 3.15%, moderate prone area of 5.85%, low prone area of 7.75%, and 81.68% are very low prone areas.